Des leviers d’action pour favoriser la biodiversité urbaine dans le cadre du processus de métropolisation - Alexandre Dejean; Aurélia Hild; Roxana Rotaru; Martha Sasso; Djamila Vuilleumier-Papaloïzos; Philippe Clergeau (Cybergeo, 2019)
Today, biodiversity is seen as a necessary element in the construction of sustainable and resilient cities, particularly through the multiple services it provides to urban dwellers. The weakness of the consideration in public policies, questioned us on the interest of the new level of decision as that of the metropolis, in full formalization. We asked ourselves the question of the acceptability of this biodiversity in the emergence of the metropolis, in particular by seeking the levers or the brakes on this acceptability which conditions the decision making.In order to answer them, we have built a cross analysis of four case studies in four French metropolises: Bordeaux, Montpellier, Nantes and Strasbourg. We met different actors of metropolis, city and associations. Our interviews led to the identification of six levers of acceptability: The culture of nature, the communication, the participative democracy, the law, the economy and the administrative organization. In view of the answers obtained, we discuss these different categories and the concrete recommendations that emerged from them.